Left and right : the significance of a political distinction / Norberto Bobbio ; translated with an introduction by Allan Cameron. - Bobbio, Norberto, 1909- (Polity, 1996)
Following the collapse of communism and the decline of Marxism, some commentators have claimed that the distinction between left and right can now be forgotten. In this book, one of Europe's foremost political thinkers challenges that view